Structural evolution of Eu-doped hydroxyapatite nanorods monitored by photoluminescence emission - Andre, R. S.; Paris, E. C.; Gurgel, M. F. C.; Rosa, I. L. V.; Paiva-Santos, C. O. [UNESP]; Li, M. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2012)
This paper reports the synthesis of Eu-doped hydroxyapatite (HA:Eu) resulting in particles with nanorod diameters from 9 to 26 nm using the microwave hydrothermal method (HTMW). Eu3+ ions were used as a marker in the HA network by basic hydrolysis followed by the HTMW treatment. The crystalline HA:Eu nanorod nature in a short-range order was detected by photoluminescence (PL) measurements from Eu3+ emission into the HA matrix. Thus, was possible to verify that HA crystallization is favored in a short structural order when the HTMW treatment time was increased from 0 to 40 min and that the Eu3+ substitution in the HA lattice is site-selective. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hydroxyapatite; Europium; Nanoparticles; Microwave-hydrothermal method; Photoluminescence